An Investigation of Multi-Variable Optimization Applied to the Hospitality Industry - Gao, Peng (ProQuest Dissertations & Theses, 2016)
This thesis focused on a complex multi-variable multi-objective optimization problem applied to the hospitality industry. Unlike running a normal hotel, running a condo hotel needs to make both the guests and the unit owners satisfied. To make guests happy, hotel operators try the best to fulfill requests of the guests. On the other hand, making owners happy requires that those same operators provide a transparent and balanced income summary for each owner. Appropriately balancing, these often conflicting objectives is crucial in condo hotel management. Unfortunately, even though current commercial packages claimed to contain equalization method, the result using them is negative. This thesis introduced an engineering optimization method to this problem. Several optimization methods were considered, and one that was selected as most appropriate was developed and tested with sample potential input information. The result demonstrated a marked increase in performance once optimization method was applied. Key words: multi-variable multi-object optimization, condo hotel management, equalization method, greedy algorithm.